Management’s role in facilitating - Janzen, Maria Anna Elizabeth (My University, 2011)
Transformation is of paramount importance within the South African context. It offers the potential to not only create a competitive edge for those organisations that embrace change, but also offers the opportunity to address the inequalities of the past in a constructive and pro-active manner. According to the Minerals and Petroleum Resource Development (MPRD) Act (RSA, 2002), mining companies are required to apply for a “New Mining Order Right” licence to mine from the Department of Minerals and Energy (DME). Amongst other things, in order for the DME to grant the new mining licence, mining companies need to demonstrate commitment and progress in terms of the achievement of their set transformational goals. The objective of the study was to define which management practices assist employees to embrace transformational change in the South African mining industry. Having an understanding of management’s role in facilitating transformational change will better position an organisation to ensure the achievement of their strategic transformational goals. The research method chosen was a qualitative case study conducted in the interpretive paradigm using the case study method at a single case site. The study showed that: setting the vision, mission and values; cultivating an environment of mutual trust; communicating effectively; engaging employees; embracing diversity; creating a safe environment, promoting employee wellness; and putting transformational enablers in place are important management practices that assist employees to embrace transformational change.
MBA - WBS
Keywords: Transformation in the workplace; Mining industry